2021
DOI: 10.21315/tlsr2021.32.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of Ornate Threadfin Bream (Nemipterus hexodon) in Thailand

Abstract: Ornate threadfin bream (Nemipterus hexodon) is an economically important fishery species in Southeast Asia. In Thailand, N. hexodon decreased dramatically due to overexploitation for commercial purposes. To construct an effective sustainable management plan, genetic information is necessary. Thus, in our study, the population genetic structure and demographic history of N. hexodon were investigated using 419 bp of the mitochondrial DNA sequence in cytochrome oxidase subunit I gene (mtDNA COI). A total of 142 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Similar findings have been recorded in other pelagic fishes in the region, such as ornate threadfin bream, Nemipterus hexodon ( Supmee et al, 2021 ); crescent perch, Terapon jarbua ( Chanthran et al, 2020 ), Japanese scad, Decapterus maruadsi ( Jamaludin et al, 2020 ), Russell’s snapper, Lutjanus russelli ( Klangnurak, Phinchongsakuldit & True, 2012 ); lesser spotted-leatherjacket, Thamnaconus hypargyreus ( Li et al, 2016 ) and crimson snapper , Lutjanus erythropterus ( Zhang, Cai & Huang, 2006 ). Furthermore, the drifting planktonic larva could further enhance the genetic connectivity of A. sirm in SCS, a factor attributed to the panmixia observed in the ornate threadfin bream, Nemipterus hexodon along the Gulf of Thailand coastline ( Supmee et al, 2021 ). Larval transport due to oceanic water movement during monsoons is suggested to strongly influence the population’s geographical structure ( Palumbi, 1994 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar findings have been recorded in other pelagic fishes in the region, such as ornate threadfin bream, Nemipterus hexodon ( Supmee et al, 2021 ); crescent perch, Terapon jarbua ( Chanthran et al, 2020 ), Japanese scad, Decapterus maruadsi ( Jamaludin et al, 2020 ), Russell’s snapper, Lutjanus russelli ( Klangnurak, Phinchongsakuldit & True, 2012 ); lesser spotted-leatherjacket, Thamnaconus hypargyreus ( Li et al, 2016 ) and crimson snapper , Lutjanus erythropterus ( Zhang, Cai & Huang, 2006 ). Furthermore, the drifting planktonic larva could further enhance the genetic connectivity of A. sirm in SCS, a factor attributed to the panmixia observed in the ornate threadfin bream, Nemipterus hexodon along the Gulf of Thailand coastline ( Supmee et al, 2021 ). Larval transport due to oceanic water movement during monsoons is suggested to strongly influence the population’s geographical structure ( Palumbi, 1994 ).…”
Section: Discussionsupporting
confidence: 77%
“…Chanthran et al (2020) attributed the genetic separation between the Kuala Selangor (Peninsular Malaysia) and Sandakan (Borneo) populations of crescent perch, Terapon jarbua to this factor . The same factor underlies the separation of the ornate threadfin bream, Nemipterus hexodon ( Supmee et al, 2021 ), and Russell’s snapper ( Klangnurak, Phinchongsakuldit & True, 2012 ) between the AS and the Gulf of Thailand. Similarly, A. sirm may experience this phenomenon due to the high genetic distance between the SCS and the AS.…”
Section: Discussionmentioning
confidence: 99%
“…The expectation of effective gene flow due to larval dispersal in B. boddarti was corroborated by the hierarchical analysis of genetic structure, which showed the absence of deep structuring in the Gulf of Thailand, despite the patchy distribution of mangrove habitats in the study area. The lack of genetic structuring was reported for other marine organisms in the Gulf of Thailand, such as ornate threadfin bream (Supmee et al, 2021), cobia (Phinchongsakuldit et al, 2013) and green mussel (Prakoon et al, 2010). These studies suggested that dispersal ability, water current and the lack of strong physical barrier in the area may have accounted for their findings.…”
Section: Discussionmentioning
confidence: 83%